Protodioscin Content, Degradation Kinetics, and In Vitro Digestibility of Marandu Palisadegrass Hay as were Affected by Cutting Interval of the Canopy - F. O. C. G. Coca; E. N. O. Gomes; L. Junges; L. C. V. Ítavo; L. M. Nonato; F. K. Gomes; C. C. B. F. Ítavo; G. S. Difante; A. M. Dias (Faculty of Animal Science, Bogor Agricultural University, 2022)
Even though marandu palisadegrass is widely used in Brazil, the consumption of this forage may cause photosensitization in ruminants due to the protodioscin. This study aimed to recommend a harvest cutting interval for haymaking that provides a better nutritional value and lower levels of protodioscin. The experimental treatments were four cutting intervals (21 d, 35 d, 49 d, and 63 days of regrowth period up to forage harvest). The experimental design was a completely randomized block design with 4 treatments and 4 replications. We assessed the forage production, chemical composition, in vitro digestibility, in vitro degradation kinetics, and protodioscin content. The forage accumulation rate did not differ with the increased cutting interval. The crude protein contents and in vitro digestibility of dry matter decreased linearly with the increased cutting interval in fresh and hay material. The greatest gas production in hay material was occurred in 21 d cutting interval, which was 26%, 14%, and 5% greater than cutting intervals of 63, 49, and 35 d, respectively. A linear increase was observed in protodioscin concentration in hay according to the cutting interval, which in the hay with 63 d cutting interval was 7%, 29%, and 43% greater than hays with cutting interval of 49, 35, and 21 d, respectively. In addition, protodioscin contents were lower in hay compared to fresh material. The haymaking process reduced protodioscin content in relation to forage before haymaking. Our results showed that the better condition to harvest marandu palisadegrass for hay was at 21 d. The better condition to develop a productive canopy is associated with better nutritive value and lower protodioscin content.